Chapter 1.6 The Development of Research Management and Administration in Europe: A Short History - Anna Groeninx van Zoelen (Emerald Publishing Limited, 2023)
The development of Research Management and Administration (RMA) in Europe is strongly connected with the development of the Science and Technology (S&T) policy of the European Union (EU). These policies were the result of a continuous debate between the member states and the European Commission and European Parliament. Although there is no data on the early development of RMA, there are some publications on the history of the development of the S&T policy in Europe: the excellent publication `A History of European Union Research Policy' by Luca Guzzetti ( Guzzetti, 1995 ). Guzzetti's book investigates the history of EU research policies from 1948 up to the preparation of the Fourth Framework Programme (FP) (1994–1998). The RMA aspects are constructed mainly by oral history complemented with some written sources. The history shows a gradual development of the profession unevenly spread in time and European geography. This has mainly with the EU enlargement in the same period, when new member states were connected to the FP. The profession started with a few colleagues' way back in the eighties of the last century as financial people were dealing with the first European financial reporting up to the present day where RMA is becoming a field of work attracting many new colleagues.
10.1108/978-1-80382-701-820231008; 10.1108/978-1-80382-701-820231008; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262